2020
DOI: 10.1175/jcli-d-19-0396.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Radiative Feedbacks from Internal Variability Using Multiple Regression

Abstract: The sensitivity of the climate to CO2 forcing depends on spatially varying radiative feedbacks that act both locally and nonlocally. We assess whether a method employing multiple regression can be used to estimate local and nonlocal radiative feedbacks from internal variability. We test this method on millennial-length simulations performed with six coupled atmosphere–ocean general circulation models (AOGCMs). Given the spatial pattern of warming, the method does quite well at recreating the top-of-atmosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…Since the UVic model captures the average efficiency in CMIP5 quite well (which implies that it may also emulate the large-scale, average circulation dynamics in CMIP5), it must therefore be an inferior emulator for those CMIP5 models in which ventilation dynamics vary widely from the ensemble mean ( Figure 2). Sea surface warming patterns are known to regulate the climate's transient response to forcing through their interaction with radiative feedbacks (Andrews et al, 2015;Armour et al, 2013;Bloch-Johnson et al, 2020;Ceppi & Gregory, 2019;Dong et al, 2019;Gregory & Andrews, 2016;Rose et al, 2014). Our results show that warming patterns additionally influence the climate response by damping the ocean's ability to absorb heat, on average, in coupled models.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Since the UVic model captures the average efficiency in CMIP5 quite well (which implies that it may also emulate the large-scale, average circulation dynamics in CMIP5), it must therefore be an inferior emulator for those CMIP5 models in which ventilation dynamics vary widely from the ensemble mean ( Figure 2). Sea surface warming patterns are known to regulate the climate's transient response to forcing through their interaction with radiative feedbacks (Andrews et al, 2015;Armour et al, 2013;Bloch-Johnson et al, 2020;Ceppi & Gregory, 2019;Dong et al, 2019;Gregory & Andrews, 2016;Rose et al, 2014). Our results show that warming patterns additionally influence the climate response by damping the ocean's ability to absorb heat, on average, in coupled models.…”
Section: Discussionmentioning
confidence: 70%
“…Sea surface warming patterns are known to regulate the climate's transient response to forcing through their interaction with radiative feedbacks (Andrews et al, 2015; Armour et al, 2013; Bloch‐Johnson et al, 2020; Ceppi & Gregory, 2019; Dong et al, 2019; Gregory & Andrews, 2016; Rose et al, 2014). Our results show that warming patterns additionally influence the climate response by damping the ocean's ability to absorb heat, on average, in coupled models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocean heat uptake influences the pattern of surface temperature (Haugstad et al, 2017), which in turn determines the strength of climate feedback due to the spatially heterogeneous nature of these feedbacks (Armour et al, 2013). Specifically, the increase in feedback with time appears to be in large part due to the movement of the pattern of warming away from regions of tropical convection, regions that tends to induce particularly negative climate feedbacks (Bloch‐Johnson et al, 2020; Dong et al, 2019; Zhou et al, 2017). Feedback temperature dependence, as mentioned above, can also change the slope of Δ F against Δ T .…”
Section: Introductionmentioning
confidence: 99%
“…Going to even longer variability, recent work found that the longwave feedback inferred from internal variability in CMIP5 Global Climate Models only approaches its equilibrium value on time scales longer than  10 years (Lutsko & Takahashi, 2018). A plausible explanation is that the spatial pattern of warming/ cooling associated with internal variability differs from the warming pattern under 2 CO forcing (Andrews et al, 2018), and that warming in different parts of the world triggers distinct and non-local feedbacks (e.g., surface warming in the West Pacific can change tropospheric emission in the East Pacific without directly warming the surface in the East Pacific; Bloch-Johnson et al, 2020;Dong et al, 2019). Since these dynamics imply that local atmospheric changes under internal variability are not necessarily driven by changes in local surface temperature, the same dynamics that cause seasonal OLR loops might thus also occur on longer timescales, which would complicate inferences about Earth's long-term feedbacks that are based on simple linear regression.…”
Section: Discussionmentioning
confidence: 99%